The Impact Of The E4msr (Embodiment For Motor Skills And Social Reciprocity) Intervention On The Motor And Social Reciprocity Skills Of Children With Autism - Chuah, Chia Chyn (2025)
Children with autism are often found to have poor motor skills as well as lack of social reciprocity skills. This case study aimed to investigate the impact of the E4MSR intervention on the motor and social reciprocity skills of children with autism ages four to five years old at an NGO intervention centre in Penang, Malaysia.